Measurement of Inequality of Opportunity Based on Counterfactuals - Dirk Van de gaer; Xavi Ramos (Institute for the Study of Labor (IZA), 2015)
The theoretical literature on inequality of opportunity formulates basic properties that measures of inequality of opportunity should have. Standard methods for the measurement of inequality of opportunity require the construction of counterfactual outcome distributions through statistical methods. We show that, when standard parametric procedures are used to construct the counterfactuals, the specification used determines whether the resulting measures of inequality of opportunity satisfy the basic properties.
Keywords: D3; D63; C1; 330; counterfactuals; inequality measurement; opportunities